NILAI NORMAL MONTREAL COGNITIVE ASSESMENT VERSI INDONESIA MoCAIna - Bambang Tri Prasetyo*, Silvia Francina Lumempouw**, Yetti Ramli**, Herqutanto*** (Neurona Majalah Kedokteran Neuro Sains, 2011)
INTRODUCTION INDONESIAN VERSION OF MONTREAL COGNITIVE ASSESSMENT HAVE BEEN VALIDATED AND REALIBILITY TEST WITH GOOD RESULT BUT THEY ARE STILL NO NORMALITY SCORE